Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x^4-2012(x^3-x^2+x-1)
mà 2012=x
suy ra h(2012)=x^4-x.x^3+x.x^2-x.x+2012
=x^4-x^4+x^3-x^2+x
=x^3-x^2+x
=2012(2012^2-2012+1)
=2012(2012.2011+1)
=2012^2.2011+2012
Ta có: x=2011 \(\Rightarrow\)x+1=2012
\(\Rightarrow A=x^{2011}-\left(x+1\right).x^{2010}\)\(+\left(x+1\right)x^{2009}\)\(-\left(x+1\right)x^{2008}+...\)\(-\left(x+1\right)x^2+\left(x+1\right)x-1\)
=\(x^{2011}\)\(-x^{2011}-x^{2010}+x^{2010}+x^{2009}-x^{2009}-\)...\(-x^2+x^2+x-1\)
= \(x-1=2011-1=2010\)
=
x=2012
nên x+1=2013
\(f\left(x\right)=x^{2013}-x^{2012}\left(x+1\right)+x^{2011}\left(x+1\right)-...-x^2\left(x+1\right)+x\left(x+1\right)-1\)
\(=x^{2013}-x^{2013}-x^{2012}+x^{2012}-...-x^3-x^2+x^2+x-1\)
=x-1
=2012-1=2011
Ta có: \(x=2011\Rightarrow x+1=2012\)
Khi đó, ta có:
\(H\left(x\right)=x^4-\left(x+1\right).x^3+\left(x+1\right).x^2-\left(x+1\right).x+2012\)
\(=x^4-x^4-x^3+x^3+x^2-x^2-x+2012\)
\(\Rightarrow H\left(2011\right)=-2011+2012=1\).
Vậy \(H\left(2011\right)=1\)
Cách 2:
\(H\left(x\right)=x^4-2012x^3+2012x^2-2012x+2012\)
\(=x^4-2011x^3-x^3+2011x^2+x^2-2011x-x+2011+1\)
\(=x^3\left(x-2011\right)-x^2\left(x-2011\right)+x\left(x-2011\right)-\left(x-2011\right)+1\)
\(=\left(x^3-x^2+x-1\right)\left(x-2011\right)+1\)
\(\Rightarrow H\left(2011\right)=1\)
Vậy...